2019
DOI: 10.7716/aem.v8i4.1235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Number of Phases on Electromagnetic Torque Characteristics of Transverse Flux Permanent Magnet Machines

Abstract: This paper presents an investigation on the influences of number of phases of Transverse Flux Permanent Magnet (TFPM) machines on the characteristics of developed electromagnetic torque. Electromagnetic torque is expressed in terms of the Fourier series of phase currents and internal voltages. After some algebraic and trigonometric calculations, a general equation is obtained that establishes a relationship between the electromagnetic torque ripples, number of phases and harmonic contents of both internal volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…C-core TFMs benefit from lower losses and higher torque at the cost of a more challenging manufacture [84,97]. • Claw-pole stator [8,16,25,87,95,98,[122][123][124] or claw-pole stator and rotor [85,86]. Compared to a radial machine and a mutual flux path TFM with the same volume, the claw-pole TFM offers higher torque densities and its weight is lower.…”
Section: Stator Coresmentioning
confidence: 99%
See 3 more Smart Citations
“…C-core TFMs benefit from lower losses and higher torque at the cost of a more challenging manufacture [84,97]. • Claw-pole stator [8,16,25,87,95,98,[122][123][124] or claw-pole stator and rotor [85,86]. Compared to a radial machine and a mutual flux path TFM with the same volume, the claw-pole TFM offers higher torque densities and its weight is lower.…”
Section: Stator Coresmentioning
confidence: 99%
“…Ideally, there is no magnetic coupling between phases, so they are all independent of each other. The number of phases determines the harmonics content, which causes torque ripple: considering a maximum of 6 phases, it is shown that the ripple to average torque ratio of 2-and 4-phase TFMs is more than double the ratio of 3-and 6-phase motors [122]. It must be taken into account that even if only one phase is fed with current, the cogging torque on the rotor involves all phases [82]; however, the machine can continue operating with less specific torque and more torque ripple, leading to a fault-tolerant drive [114].…”
Section: Phase Arrangement (Stacking Sectorial)mentioning
confidence: 99%
See 2 more Smart Citations
“…FEM is a method that is used to obtain the solutions of amounts that are continuous in a certain region whose changes in the region where they are continuous may be represented by partial differential equations. By using this method, it is possible to obtain the electromagnetic parameters of a generator with high accuracy [24,25]. The mesh structure in the generators was created automatically with the help of a computer program.…”
Section: Analysis Of the Performance And Cost Of The Designed Generatorsmentioning
confidence: 99%